2015
DOI: 10.1182/blood-2015-02-627356
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-17-92 controls T-cell responses in graft-versus-host disease and leukemia relapse in mice

Abstract: MicroRNAs (miRs) play important roles in orchestrating many aspects of the immune response. The miR-17-92 cluster, which encodes 6 miRs including 17, 18a, 19a, 20a, 19b-1, and 92-1, is among the best characterized of these miRs. The miR-17-92 cluster has been shown to regulate a variety of immune responses including infection, tumor, and autoimmunity, but the role of this cluster in T-cell response to alloantigens has not been previously explored. By using major histocompatibility complex (MHC)-matched, -misma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 37 publications
4
65
0
Order By: Relevance
“…To verify the NanoString data, 10 microRNAs (miR-146a, miR-30b-5p, miR-374-5p, miR-20a, miR-15a, miR-181a, miR-18a, miR-19a, miR-19b, and miR-451a) were selected for further assessment in the diagnostic verification cohort (Table 2), based on those with high FC and/or reported in the literature to be implicated in GvHD, T-cell function, or the inflammatory response (13, 2632). …”
Section: Resultsmentioning
confidence: 99%
“…To verify the NanoString data, 10 microRNAs (miR-146a, miR-30b-5p, miR-374-5p, miR-20a, miR-15a, miR-181a, miR-18a, miR-19a, miR-19b, and miR-451a) were selected for further assessment in the diagnostic verification cohort (Table 2), based on those with high FC and/or reported in the literature to be implicated in GvHD, T-cell function, or the inflammatory response (13, 2632). …”
Section: Resultsmentioning
confidence: 99%
“…Because the impact of mitochondrial proteins on clonal expansion of activated T cells has been described (23), the regulation of different targets in functionally different pathways by miR-181a (phosphatases downstream of TCR, regulators of mitochondrial apoptosis, and PTEN among others) may result in a more complex phenotype, although the relative importance of each individual pathway remains to be determined. Interestingly, Wu et al (6) observed BCL-2 and PTEN as a target of the miR-17-92 cluster. Whereas the threshold for TCR signaling may be lowered by miR-181a, its expression has to be limited to maintain the balance of pro-and anti-apoptotic signals in activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased miR-146a expression in donor T cells prevents from GvHD development by targeting TNFR-associated factor 6, leading to reduced TNF transcription (5). It has also been shown that blocking the miR17-92 cluster alleviates aGvHD while preserving the graftversus-leukemia (GvL) effect (6).…”
mentioning
confidence: 99%
“…It indicated that miR-153 might be related to some immune-related diseases, including GVHD. The majority of the miRs related to aGVHD have been shown to function in T or B lymphocytes [11, 12, 22]. However, IDO might inhibit aGVHD development through various types of cells in addition to lymphocytes, such as dendritic cells (DCs), mesenchymal stem cells (MSCs) and myeloid-derived suppressor cells (MDSCs).…”
Section: Discussionmentioning
confidence: 99%